Do Readers Remember What Story Characters Remember?. Issue 1 (2nd January 2020) - Houghton, Kenneth J.; Klin, Celia M.
ABSTRACT: The current study examined whether readers encode the thoughts of story characters. Participants read narratives in which characters were described as either needing or not needing to remember a list of words. Across several experiments readers recalled more words in a free recall task when the story character was described as making an effort to remember the same words. This occurred during both self-paced reading and when reading time was fixed. Much like readers encode, and perhaps simulate, other aspects of a story character's experience, such as their physical movements, speaking and reading speed, and tactile experiences, we demonstrate that the readers' mental representation is influenced by a story character's cognitive processes. Readers remember what story characters remember.